Effect of financial performance and disclosure of carbon emissions on Environmental Performance with Good Corporate Governance as a moderation variable - Viulina, Audira Eri; Utaminingtyas, Tri Hesti; Ulupui, I Gusti Ketut Agung (Business and Investment Review, 2023)
This study aims to examine the effect of financial performance and carbon emissions disclosure on environmental performance, and to examine the role of good corporate governance in moderating this relationship. This study uses quantitative methods with secondary data in the form of annual reports of non-financial companies listed on the Indonesia Stock Exchange in 2019-2021. The sample was determined using purposive sampling method and produced 132 samples. The results of this study indicate that financial performance has a positive and significant effect on environmental performance, and disclosure of carbon emissions has a positive and significant effect on environmental performance. However, good corporate governance cannot moderate the relationship between financial performance and carbon emission disclosure on environmental performance.